Youths’ intention towards Online Food Delivery (OFD) services in Kota Kinabalu / Michelina David ... [et al.] - David, Michelina; Mogindol, Spencer Hedley; Bidder, Christy; Kibat, Silverina Anabelle; Fatt, Boyd Sun (2021)
The business of online food delivery (OFD) services has grown rapidly over the years and more so during the COVID-19 pandemic. To date, a significant amount of research works relating to OFD services have been conducted, however, not many have focused on the intention of using OFD services especially from the youths’ perspective. Hence, the purpose of this study is to examine youth’s intention of using OFD services. The study applied a quantitative approach and the unit of analysis for this study is the youths between 18 to 40 years old, as the potential users of OFD services living in Kota Kinabalu, Sabah. Through the cross-sectional data collection approach and purposive sampling technique, 346 samples were collected via an online survey questionnaire. The survey questionnaire was adopted from previous studies with minor modifications, validated and pilot tested. A total of 346 responses were collected and analysed using descriptive and multiple regression analysis. The results indicated all the predictors (convenience motivation, time-saving motivation, price-orientation motivation, and hedonistic motivation) significantly affect youth’s intention towards OFD services. The study contributes to the existing literature on OFD and practical implications to the food industry, food delivery services, and marketers from the youths’ perspective.